Стандарти кодованих архівних опису та контексту (проблема впровадження) - Марченко, П. (Архіви України, 2009)
The implementation problem of the international standards encoded the archival description and the context (EAD, EAC) is considered. The decision of the problem demands creation of the certain descriptive system of electronic archive. The primary goals, which are necessary for solving at creation of descriptive system, and also approaches to their decision are outlined.